Cable connector assembly - WU JERRY (2013)
A cable assembly (100) includes a housing (10) consisted of a first shield part (1) assembled to a second shield part (2) to form a receiving space, said receiving space including a hollow portion (110) and a mating port (120) located in front of the hollow portion; a pair of first and second printed circuit boards (31, 32) received in the receiving space, both the pair of printed circuit boards having mating interfaces extending into the mating port and mounting portions located within the hollow portion; a spacer (4) interposed between the pair of first and second printed circuit boards (31, 32), said spacer (4) cooperating the housing (10) to fix the pair printed circuit boards within the receiving space; a plurality of cables (7) separated into two groups and coupled to the mounting portions of the pair of first and second printed circuit boards, respectively. The two group of cables offset from one another along a vertical direction and extend rearward from the housing.